Accelerated onset of viral transcription in adenovirus-infected HeLa cells treated with the tumor promoter 12-O-tetradecanoyl-phorbol-13-acetate. - Carter, T H (1984)
When adenovirus type 5-infected HeLa cells were exposed to the tumor promoter 12-O-tetradecanoyl-phorbol-13-acetate, short pulse-labeling with [3H]uridine in vivo and [3H]UTP incorporation by isolated nuclei in vitro were both consistent with a decreased latent period before initiation by RNA polymerase at early viral promoters. Acceleration was not dependent upon concurrent protein synthesis and could not be attributed to rapid entry of virus into the cell nucleus. 12-O-tetradecanoyl-phorbol-13-acetate suppressed the transcription-delay phenotype of the E1a mutant, hr1, without restoring its ability to replicate.